The Effect of Lactobacillus GG (LGG) on Acute Diarrheal Illness in the Pediatric Emergency Department (PED) - Nixon, Abigail F. (2012)
OBJECTIVE: The purpose of this study was to evaluate the effectiveness of the probiotic Lactobacillus GG (LGG) in reducing the duration of acute infectious diarrhea in the pediatric emergency department (PED). METHODS: We conducted a double blind randomized controlled trial of children 6 months to 6 years presenting to the PED with a complaint of diarrhea. Patients were randomized to receive either placebo or LGG powder twice daily for 5 days. With each dose, parents recorded the stool history in a home diary and were followed-up daily by a blinded researcher. Groups were compared in terms of time to normal stool and number of diarrheal stools. RESULTS: Of 155 patients enrolled, 129 completed the study: 63 in the LGG group and 66 in the placebo group. There was no significant difference in the median (IQR) time to normal stool (LGG 60 hrs [37,111] vs placebo 74 hrs [43,120] p=0.37) or the number of diarrheal stools (LGG 5.0 [1,10] vs placebo 6.5 [2,14] p=0.19). Among children who presented with >2 days of diarrhea, the LGG group returned to normal stool earlier (LGG 51 hrs [32, 78] vs placebo 74 hrs [45,120], p=0.02), had fewer episodes of diarrheal stools (LGG 3.5 [1.0,7.5] vs placebo 7 [3.0,16.3] p=0.02) and were 2.2 times more likely to return to normal stool (95%CI 1.3-3.9, p=0.01) than children in the placebo group. CONCLUSION: LGG may reduce the duration of acute diarrheal illness among children presenting with >2 days of symptoms.